Natural Solutions for Revitalizing Aquatic Ecosystems: The Case of the Three Ponds in Maribor - Vovk, Ana (Podeželje, 2026)
In this article, we present natural solutions (NBS) that offer an effective framework for revitalizing rural water ecosystems by mimicking natural processes to restore water quality and habitat functions. The introduction presents the principles of NBS, which are synonymous for imitation of nature and emphasize the restoration of the original hydrological and ecological dynamics to exploit the self-cleaning capabilities of ecosystems. We linked the contribution to the Revitalization of Three Ponds with NBS project, which we carried out in 2024, thus demonstrating concrete possible solutions for the restoration of aquatic ecosystems. It turned out that we can use the best international practices of nature conservation and biotechnical interventions, which include the reintroduction of riparian vegetation, the use of stone weirs, and the creation of substrate heterogeneity for water oxygenation, sequestration of excess nutrients, and increased biodiversity. The status of the protected area and the management regime of Trije ribniki, which includes habitat conservation, water resource management, and community participation, are also considered. The results of the study are useful in rural areas, as locally sourced materials can provide multifunctional ecosystem services, from flood mitigation to educational awareness.